Pengaruh Model Pembelajaran Cooperative tipe Make a Match Terhadap Penguasaan Materi Siswa pada Mata Pelajaran Pendidikan Agama Islam Dan Budi Pekerti - Wulan WidiAstuti; Tri DianNurhalimah; Ahmad Fauzi; Badru Sohim (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2025)
This research is motivated by the low mastery of learning material among students, which is caused by the lack of varied, creative, and engaging learning strategies. As a result, students are less interested and face difficulties in understanding classroom material. The study aims to analyze the influence of the Make a Match type cooperative learning model on students’ mastery of material in Islamic Religious Education and Character subjects in grade V at Bukanagara 1 State Elementary School. This research uses a quantitative approach with a pre-experimental design method, specifically the one-group pretest-posttest design. The research sample involved fifth-grade students. The results showed that the average pretest score was 2.63 (medium category), while the posttest score increased to 4.19 (very high category). The pretest and posttest data were normally distributed, with significance values of 0.796 and 0.181 respectively (˃ α = 0.05). The homogeneity test showed a significance value of 0.070, indicating equal variance. Simple regression analysis results showed a significance value of 0.758 (˃ α = 0.05), meaning there is a significant difference between pretest and posttest scores. Therefore, it can be concluded that the Make a Match cooperative learning model positively influences students’ mastery of learning material.